2002
DOI: 10.1254/jjp.88.256
|View full text |Cite
|
Sign up to set email alerts
|

Role of Rho-Associated Protein Kinase and Histamine in Lysophosphatidic Acid-Induced Airway Hyperresponsiveness in Guinea Pigs

Abstract: ABSTRACT-Inhalation of oleoyl lysophosphatidic acid (LPA) induced airway hyperresponsiveness to acetylcholine (ACh). In contrast, palmitoyl and stearoyl LPA exerted minimal effects. Airway hyperresponsiveness was inhibited by inhalation of Y-27632, an inhibitor of Rho-associated protein kinase (ROCK). Mepyramine, an H1 histamine receptor antagonist and ketotifen, an inhibitor of histamine release and H1 histamine receptor antagonist, also inhibited airway hyperresponsiveness induced by LPA; however, aspirin fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 25 publications
(21 reference statements)
0
24
0
4
Order By: Relevance
“…The effect of lysophosphosphatidic acid, a known activator of ROCK, is shown for comparison. [33][34][35] Inactivation of MYPT1 by 5-HT was inhibited by the ROCK inhibitor, Y27632, in a dose-dependent manner ( Figure 1B). Bovine pulmonary artery SMC contain both SERT and a variety of 5-HT receptors, including the 5-HT1B/1D receptor as determined by polymerase chain reaction (unpublished data).…”
Section: -Ht Activates Rockmentioning
confidence: 96%
“…The effect of lysophosphosphatidic acid, a known activator of ROCK, is shown for comparison. [33][34][35] Inactivation of MYPT1 by 5-HT was inhibited by the ROCK inhibitor, Y27632, in a dose-dependent manner ( Figure 1B). Bovine pulmonary artery SMC contain both SERT and a variety of 5-HT receptors, including the 5-HT1B/1D receptor as determined by polymerase chain reaction (unpublished data).…”
Section: -Ht Activates Rockmentioning
confidence: 96%
“…In contrast, LPA 1 and LPA 2 showed broad ligand specificity (9). We also reported that differential activation by LPA species was evident in airway responsiveness to acetylcholine; furthermore, LPA-induced airway hyperresponsiveness was attributable to histamine release (10). From these points, we also hypothesize that LPA-indiced histamine release may occur via an LPA receptor(s).…”
Section: Introductionmentioning
confidence: 77%
“…Initial studies in that area begin in the late 1970s and have started by looking at the combined effect of spasmogens on different measures of lung function in animals (45,46,57,99,102,112,131,152,180,181,192,208,209,224,244), as well as in humans (49,68,97,101,110,156,158,194,202,240). Apart from an interactive synergism at the level of ASM contraction, many other factors can account for these in vivo interactive synergisms.…”
Section: Interactive Synergisms Between Spasmogensmentioning
confidence: 99%